The Effect of Gender Equality on Economic Growth In West Sumatera 2017-2020 - Muhammad Nabiel (HUMANISMA : Journal of Gender Studies, 2021)
The Sustainable Development Goals (SDGs) goal is to support an inclusive and sustainable economy, a full and productive workforce, decent work for all, and gender activities. In 2020, West Sumatra Province was one of the provinces with the 4th highest Gender Development Index (GDI) in Indonesia and was the highest GDI in Sumatra Island. However, West Sumatra’s economic growth tends to decline in the 2017-2020 period. Several studies have shown a positive relationship between gender and economic growth. Therefore, this study aims to get an overview of gender in education, economy, and technology and find information about gender on economic growth in West Sumatra Province for the 2017-2020 period. This study uses panel data regression analysis based on the National Socio-Economic Survey (SUSENAS) data for 2017-2020. The results show that gender in the economic and technological fields has generally decreased in 2017-2020. Gender equality in education, represented by the average length of schooling for women to men, has a significant negative effect. On the other hand, in the health sector, which is represented by the ratio of life expectancy of women to men, it has a significant positive effect on economic growth. Salah satu tujuan Sustainable Development Goals (SDGs) adalah mendukung pertumbuhan ekonomi yang inklusif dan berkelanjutan, tenaga kerja penuh dan produktif, pekerjaan yang layak untuk semua, dan kesetaraan gender. Pada tahun 2020 Provinsi Sumatera Barat merupakan salah satu provinsi dengan nilai Indeks Pembangunan Gender (IPG) tertinggi ke-4 di Indonesia dan merupakan IPG tertinggi di pulau Sumatera. Namun demikian pertumbuhan ekonomi Sumatera Barat cenderung mengalami penurunan dalam periode 2017-2020. Beberapa penelitian menunjukkan adanya hubungan positif antara kesetaraan gender dengan pertumbuhan ekonomi. Untuk itu penelitian ini bertujuan melihat gambaran umum terkait kesetaraan gender pada bidang pendidikan, kesehatan, ekonomi dan teknologi serta menganalisis pengaruh kesetaraan gender terhadap pertumbuhan ekonomi di Provinsi Sumatera Barat periode 2017-2020. Penelitian ini menggunakan analisis regresi data panel berdasarkan data Survei Sosial Ekonomi Nasional (SUSENAS) periode 2017-2020. Hasil penelitian menunjukkan secara umum kesetaraan gender pada bidang ekonomi dan teknologi mengalami penurunan pada periode 2017-2020. Kesetaraan gender pada bidang pendidikan yang dalam penelitian ini diwakilkan oleh rasio rata-rata lama sekolah perempuan terhadap laki-laki signifikan berpengaruh negatif. Sebaliknya kesetaraan dalam bidang kesehatan yang diwakilkan dengan rasio angka harapan hidup perempuan terhadap laki-laki signifikan berpengaruh positif terhadap pertumbuhan ekonomi.